1970
DOI: 10.4314/ejhs.v29i2.12
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Abnormality and Associated Factors in Diabetic Patients at Jimma University Specialized Hospital, Jimma, Southwest Ethiopia: A Comparative Cross-sectional Study

Abstract: BACKGROUND: Diabetes mellitus is a group of heterogeneous disorders of multiple etiologies characterized by chronic hyperglycemia resulting from defects in insulin secretion and/or insulin action. Diabetes mellitus has been reported to disturb normal hemostasis by various mechanisms. However, data on hemostasis of diabetic patients in the study area are lacking. This study was aimed at determining hemostatic profile and associated factors of hemostatic abnormality in diabetic patients.METHODS: A comparative cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…A comparative cross-sectional study conducted in a different part of the world also revealed that there is a shortening of PT and aPTT values among T2DM patients. This study finding is supported by different studies conducted by Ankalayya et al in India, 45 Mariappan et al in India, 46 Karim et al in Bangladesh, 47 Ephraim et al in Ghana, 37 Pan et al in China, 48 Sapkota et al in Nepal, 49 Asrat et al in Ethiopia, 40 and Ambelu et al in Ethiopia, 24 which showed that T2DM patients were presented with significant shortening of PT and aPTT.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…A comparative cross-sectional study conducted in a different part of the world also revealed that there is a shortening of PT and aPTT values among T2DM patients. This study finding is supported by different studies conducted by Ankalayya et al in India, 45 Mariappan et al in India, 46 Karim et al in Bangladesh, 47 Ephraim et al in Ghana, 37 Pan et al in China, 48 Sapkota et al in Nepal, 49 Asrat et al in Ethiopia, 40 and Ambelu et al in Ethiopia, 24 which showed that T2DM patients were presented with significant shortening of PT and aPTT.…”
Section: Discussionsupporting
confidence: 79%
“… 44 In addition to this, studies that are conducted in different parts of the world supported the presence of thrombocytopenia among T2DM patients. A comparative cross-sectional study conducted by Pan et al in China, 48 Madan et al in India, 55 and Asrat et al in Ethiopia 40 showed that T2DM patients were presented with thrombocytopenia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the present study, protein C and S activity was significantly lower in the diabetic rats than in the controls. It is thought that these proteins undergo structural changes caused by non-enzymatic glycation, which results in dysfunction [37]. However, in the present study, these deficiencies in plasma protein C and S in diabetic rats were significantly reversed after they received sildenafil.…”
Section: Resultscontrasting
confidence: 71%
“…Higher glycemic levels in the hypocoagulable group might monitoring of acute conditions. 11,[16][17][18][19] Therefore, TEG might be less sensitive and less specific in detecting hemostasis abnormalities in subjects without acute critical comorbidities. Although several studies indicated significant associations between acute and chronic hyperglycemia with hemostasis abnormalities, those associations were not consistently found in all parameters of hemostasis and all subsets of T2DM patients.…”
Section: Normocoagulablementioning
confidence: 99%